PENGARUH LATIHAN MENENDANG MENGGUNAKAN BEBAN ANKLE WEIGHT TERHADAP PENINGKATAN KECEPATAN TENDANGAN DEPAN SISWA EKSTRAKURIKULER PENCAK SILAT DI MTSN 4 BLITAR - Permana, Felix Reza; Supriatna; Yulingga Nanda Hanief (Journal Sport Science Indonesia, 2023)
This research was made to determine the increase in the speed of the front kick in the sport of pencak silat. In this study using the experimental method. Methods in collecting data in this studyusing tests and documentation. The test used is the front kick test. The test was given before(pre-test) and after(post-test) students are given treatment. The treatment in question is giving kicking exercises using weightsankle weight ½ kg held for 8 weeks, 22 meetings with a frequency of 3 treatments a week. Collecting data in this study students kicked with the strongest leg that had been given treatment by kicking at maximum speed for 10 seconds. On resultspre-test In this study, the lowest kick obtained was 11 kicks and the highest was 16 kicks. With an average of 14 kicks. As for resultspost-test getting the lowest kick that is 12 kicks and the highest as many as 18 kicks with an average of 15 kicks. So the results of this study are expected to be a guideline for trainers and executors of pencak silat in practicing front kick speed. Keyword: front kick speed, angkle weight, pencak silat